Laser-induced fabrication of porous gold nanoshells. Issue 43 (29th October 2018) - Park, Tae-Hyeon; Jang, Du-Jeon
Abstract : Hollow and porous gold nanoshells with high surface-enhanced Raman scattering efficiency have been fabricated through utilizing nanosecond laser irradiation. Abstract : Pulse-laser irradiation is a promising approach to fabricate gold nanostructures with unique morphologies. Hollow and porous gold nanoshells with high surface-enhanced Raman scattering efficiency have been produced via irradiating SiO2 @Au@SiO2 nanoparticles with nanosecond laser pulses; the synthetic strategy mainly relies on the laser-induced surface melting of gold nanoparticles.